EFEK BERBAGAI MINYAK PADA METABOLISME KOLESTEROL TERHADAP TIKUS WISTAR - Ni Wayan Bogoriani; Ketut Ratnayani (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2015)
This study was conducted over 10 weeks using several types of oils containing unsaturated fatty acids, saturated fatty acids and trans fatty acids, namely coconut oil, bulk oil, used cooking oil and pig fat. Animal tests were used to determine the effects of various oils on the metabolism of cholesterol in wistar rats. The study design was a randomized post-test only control group design, conducted in mice. Twenty-five rats were divided into five groups: control, treatment 1, treatment 2, treatment 3 and treatment 4, each of 5 rats. The control group was given standard diet only, treatment- 1 standard food and coconut oil 2.5 ml / day, treatment-2 standard food and bulk oil 2.5 ml / day, treatment-3 standard food and used cooking oil 2.5 ml / day and the treatment-4 standard food and pig fat 2.5 ml / day. After 10 weeks of treatment their blood plasm samples were taken for examination for total cholesterol, LDL, HDL, triglycerides, VLDL cholesterol, and the ratio of total / HDL. The results showed an increase in total cholesterol, LDL, triglycerides, VLDL, the ratio of total cholesterol / HDL and a decrease in blood plasm HDL cholesterol significantly (p <0.05) in the treatment of waste cooking oil compared with the control and other treatments. Based on these results it can be concluded that the used cooking oil has the potential to cause oxidative stress and inflamation which is a risk factor for atherosclerosis formation.